O ensino de Filosofia no atual contexto da reforma do ensino médio a partir do pensamento complexo de Edgar Morin - Santana, Larissa Ribeiro de (Universidade Federal do Tocantins, 2023)
From the perspective of Edgar Morin's thinking, highlighting his writing on the Seven Knowledges for future education, imbued with a complex thought, on the agenda for a future education, this work presents, through a bibliographical, documentary and experimental analysis, reflections on the past, present and future of Brazilian education and in Tocantins territory, essentially for the final stage of basic education, high school and, above all, the pedagogical authority of Philosophy in this context. The approach presents the constructions and deconstructions in different Brazilian historical periods and the link between curricula and economic, social, religious, ideological interests, always aligned with the power relations of moments lived in Brazil, distancing themselves, in most cases, from the search for a humanized teaching and learning process. Thus, it demonstrates the dissonance operated between what was intended for the so-called reform of Brazilian secondary education and what was purposefully consolidated after the enactment of Law n. 13.415/17, moving away from what Morin recommended for a humanized education for the future and a return to the gap in the teaching of philosophy for education in Brazil. It covers the redesigned proposal for the high school curriculum in the state of Tocantins and presents a streamlined reading of the first resolution that institutes the curricular document for the Territory of Tocantins – DCT-TO - Secondary Education Stage, guides its implementation and provides other measures. Still, it reflects the view of teachers in the area of applied human and social sciences of a High School Center, under this proposal regarding the application of the final product of this study, which is to pedagogically present the structure to which the reform of high school is proposed and the great challenge of establishing a single curriculum for plural and diverse realities.